Exploring the effectiveness of cognitive behavioral therapy for Vietnamese adolescents with anger problems - Bui, Huyen Thi; Mackie, Lynn; Hoang, Phuoc Anh; Tran, Thu Thi (Kasetsart Journal of Social Sciences, 2019)
The evidence base for cognitive behavioral therapy (CBT) is promising for the treatment of anger in both adults and children in most European and Western countries. The goal of the current study was to explore the effectiveness of this therapeutic approach for anger problems in Vietnam as a non-Western culture and non-English speaking country. A randomized controlled trial was undertaken with 40 adolescents for three months, using different CBT techniques. A medium effect size of .64 (Cohen's d) was found for a CBT intervention. Anger management skills of older adolescents (aged from 14 to 16) improved more than those of younger adolescents (aged from 12 to 13). The findings of the current study replicated previous studies regarding the high cost-effectiveness of CBT intervention for anger problems in children and adolescents. Furthermore, the suitability of the group CBT format for the treatment of anger within this study was consistent with other studies as well. This adds valuable evidence to the paucity of CBT literature on culturally responsive CBT in diverse populations. Despite this, more research is needed to produce evidence-based CBT for other Asian countries as well as other populations.